THE POTENTIAL OF Enhalus acoroides AS A BIOSTIMULANT TO ENHANCE MAIZE GROWTH AND DROUGHT TOLERANCE - Made Pharmawati; Luh Putu Wrasiati; I Made Anom Sutrisna Wijaya; Kadambot.H.M. Siddique (SEAMEO BIOTROP, 2025)
HIGHLIGHTS- Biostimulant Potential of Enhalus acoroides- Positive Effects of E. acoroides on Maize Growth- Reduction in H2O2 (Oxidative Stress) by Enhalus acoroides extractABSTRACTDrought poses a significant challenge to crop productivity, with maize particularly vulnerable. Enhancing maize tolerance to drought stress is crucial, and one promising approach involves using biostimulants derived from natural sources. The seagrass Enhalus acoroides is a potential biostimulant due to its rich phytochemical composition, including phenols, tannins, flavonoids, and pigments such as chlorophyll, lutein, pheophytin, and beta-carotene. These compounds exhibit antioxidant activity, suggesting their potential role in enhancing plant resilience to drought stress. This study evaluated the effects of E. acoroides extract on maize growth under drought conditions during the seedling phase and analyzed biochemical changes in maize plants treated with the extract. The extract was prepared using 10% dried E. acoroides leaves with a chloroform-to-ethanol solvent ratio of 9:1 (v/v) and subsequently dissolved in distilled water for final concentrations of 0.05%, 0.1%, 0.15%, 0.2%, and 0.25%. The results demonstrated that E. acoroides extract enhanced plant height, increased shoot and root fresh and dry weights. Additionally, plants sprayed with E. acoroides extract exhibited higher total sugar and protein content in the shoots as compared to non-sprayed plants. Under 20% polyethylene glycol (PEG)-induced drought stress, control plants showed severe leaf wilting, whereas extract-treated plants only had mild wilting. The chlorophyll, reducing sugar, total N, and tocopherol contents were also higher in extract-treated plants under PEG stress than in untreated controls. These findings indicate the potential of E. acoroides extract as a biostimulant for improving drought tolerance in maize.